PERAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI PEMODERASI DALAM MEMPREDIKSI PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP AGRESIVITAS PAJAK DI INDONESIA: KAJIAN TEORI LEGITIMASI - Achmad Badjuri; Jaeni Jaeni; Andi Kartika (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2021)
This study was conducted to examine the effect of profitability and company size with Corporate Social Responsibility as moderation, the object of research used by manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2017 period. The number of samples selected was 179 observations determined using the purposive sampling method. The analysis technique used is Moderated Regression Analysis. The results of the analysis of this study stated that profitability and firm size had a significant negative effect on tax aggressiveness while for moderating variables Corporate Social Responsibility strengthened profitability and weakened company size towards tax aggressiveness